A Qualitative Literature Review on the Integration of ICT in Education: Challenges, Opportunities, and Future Directions - Yovi, Febri Yonanda; Zulfahmi, Ali Mal; Syafitri, Widya; Sesmiarni, Zulfani (STIT Ahlussunnah Bukittinggi, 2025)
The use of Information and Communication Technology (ICT) in English language learning at the primary school level is becoming increasingly important in line with digital developments and the demands of the Merdeka Curriculum. This study aims to analyze the effectiveness of Information and Communication Technology (ICT) in improving English proficiency among primary school students through a directed literature review of three experimental studies. These studies examine the use of visual media, interactive multimedia, and game-based learning as Information and Communication Technology (ICT) based learning approaches. Data were analyzed using thematic-comparative techniques to identify patterns across findings. The analysis shows that Information and Communication Technology (ICT)consistently has a positive impact on improving vocabulary, listening skills, speaking skills, and student motivation. Visual media proves effective in supporting basic vocabulary acquisition, interactive multimedia enhances listening and speaking performance, while game-based learning significantly boosts motivation and student interaction. This study concludes that systematic Information and Communication Technology (ICT) integration has strong potential to improve the quality of English learning at the primary level. The study recommends selecting Information and Communication Technology (ICT) media appropriate to learning objectives and providing teacher training to optimize Information and Communication Technology (ICT) use in classroom settings.